The nature and usefulness of patient experience information in producing guidance about interventional procedures. Issue 6 (25th September 2012) - Campbell, Bruce; Chambers, Emma; Kelson, Marcia; Bennett, Sue; Lyratzopoulos, Georgios
Abstract : Objectives: To evaluate the nature of patient experience input and its perceived usefulness to members of a national Advisory Committee in making decisions about the efficacy and safety of new interventional procedures. Design: Survey of Advisory Committee members about the nature and usefulness of patients' responses to a patient experience semistructured questionnaire. Setting: Interventional Procedures Programme, NICE. Participants: 16 Committee members who assessed responses to 73 patient experience questionnaires. Main outcome measures: Judged nature and usefulness of patient responses to different questions about the experience of patients in using one of nine different procedures. Findings: Most patient responses were scored as useful: <20% were scored as 'unhelpful' or 'very unhelpful.' Committee members felt that patient responses most often supported other evidence but provided no new insights (52–68% of responses for 11 of the 12 questions). Responses to one question (effects of the procedure on specified areas of life) gave new and original evidence which was not present in the literature or expert opinions in 7% cases. Responses to eight of the 12 questions provided insights into sociocultural or equalities issues in 1–7% of cases. Conclusions: Obtaining patient experience to inform guidance development is complex but provides generally useful supporting evidence and some new insights not available from other evidence. Further research should aim to further develop and validate different methods to obtain patient experience input. The impact of patient experience information on how the Committee decides about whether a procedure is efficacious and/or safe should be made explicit.